2009
DOI: 10.1080/13102818.2009.10818394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Stress on Growth and Flowering of Ornamental Annual Species

Abstract: In 2008, a series of experiments were performed at the Institute of Ornamental Plants -Sofia in greenhouse conditions that tested the influence of salt stress on species of annual plants -Tagetes patula and Ageratum mexicanum. The plants were cultivated in pots under normal soil conditions and salt stress was induced by adding solutions with different concentrations of NaCl (0.4%, 1.2% and 2.0%). The following results were obtained:• The suppression of plant growth increases with the increase of NaCl concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 2 publications
4
13
0
1
Order By: Relevance
“…According to Munns & Tester (), even moderate salinity stress affects reproductive development, such as early flowering or a reduced number of florets. Similar responses have been cited in Zapryanova & Atanassova (), who observed that plants treated with NaCl have earlier and shorter blooming period than non‐treated plants. Katerji et al .…”
Section: Discussionsupporting
confidence: 88%
“…According to Munns & Tester (), even moderate salinity stress affects reproductive development, such as early flowering or a reduced number of florets. Similar responses have been cited in Zapryanova & Atanassova (), who observed that plants treated with NaCl have earlier and shorter blooming period than non‐treated plants. Katerji et al .…”
Section: Discussionsupporting
confidence: 88%
“…According to Munns and Tester (2008), even moderate salinity stress affects reproductive development, such as earlier flowering or a reduced number of florets. In our case, the increased number of inflorescences at the end of the experiment in plants subjected to saline stress alone may have been due to earlier blooming rather than a higher intensity of flowering, as seen in many other ornamental species exposed to saline conditions (Zapryanova and Atanassova, 2009). C. laevis plants can cope with water shortage or saline irrigation with mo great loss of their ornamental value, as has been cited for other species (Henson et al, 2006;Álvarez et al, 2012).…”
Section: Discussionmentioning
confidence: 71%
“…A concentração elevada de íons na água de irrigação e consequentemente sua acumulação no substrato, pode ter ocasionado desbalanço iônico, causando toxidade às plantas e decréscimo no crescimento e na produção de biomassa, por restringir à aquisição de elementos essenciais a nutrição da planta (Zapryanova & Atanassova, 2009). Quando a acumulação de íons, a exemplo do Cl -e Na + se dá nas folhas, inibe a atividade de enzimas envolvidas nos processos fotossintéticos, comprometendo o metabolismo de carboidratos que irão refletir diretamente na produção de biomassa (Larcher, 2006).…”
Section: Resultsunclassified